Verglüht der Stern der Modern Monetary Theory? - Ralf Fendel; André Schmidt (Wirtschaftsdienst, 2023)
Seit dem vergangenen Jahr ist die Infl ation, die aufgrund der Intensivierung des Wettbewerbs durch die Globalisierung in der ökonomischen Diskussion als nahezu ausgestorben galt, wieder zurück. Es stellt sich die Frage, inwieweit die Modern Monetary Theory (MMT) einen substanziellen Beitrag zur gegenwärtigen makroökonomischen Diskussion liefern kann, oder ob durch die Stagfl ation ihre Popularität schrittweise zurückgedrängt wird. Der Beitrag setzt sich dabei kritisch mit der MMT und der von ihr betonten fi skalischen Dominanz auseinander. – – The paper provides a critical analysis of Modern Monetary Theory (MMT). Facing the current macroeconomic problems of supply shocks caused by the Corona pandemic and the war in the Ukraine and its consequences on infl ation, the authors ask whether the MMT could seriously infl uence macroeconomic policymaking. Based on a brief analysis of the historical roots of MMT, the authors show substantial economic problems with this theory. Especially the non-consideration of infl ation issues, the inadequacy of tax policy, the problems of open economies, and the neglected problems of the New Political Economy increase the doubts about the suitability of the MMT for overcoming the current economic challenges.
Keywords: E40; E52; E62; 330; Neue Geldtheorie